Technology-Based Learning Management In Improving Learning Outcomes In Junior High Schools - Usup Supriatna; Ika Kartika; Opan Arifudin (International Journal of Science Education and Technology Management, 2025)
This study aims to investigate the impact of technology-based learning management on student learning outcomes at Madrasah Tsanawiyah (Islamic junior high school). This study uses a qualitative research method with a case study approach. Data were obtained through in-depth interviews with 12 teachers and 20 students at Madrasah Tsanawiyah (Islamic junior high school) who have used technology-based learning management. The results of the study indicate that technology-based learning management can improve student learning outcomes in several ways, namely: (1) improving the quality of teaching materials through e-learning; (2) increasing student learning motivation through game-based learning; and (3) improving students' critical thinking skills through project-based learning. The results of this study also indicate that Madrasah Tsanawiyah teachers need to be given training and support to improve their skills in using technology in the learning process.